Buoyancy driven double diffusive moisture convection inside the fluid-porous-solid sandwiched building enclosure containing internal heating sources. (August 2018) - Hu, Jiang-Tao; Mei, Shuo-Jun; Liu, Di; Zhao, Fu-Yun; Wang, Han-Qing
Highlights: Solar energy exploitation was implemented by building porous walls. Buoyancy driven double convection induced inside sandwiched enclosure. Thermal and solutal buoyancy forces aid each other for most situations. Average Nusselt and Sherwood numbers increase with Rat, N, Krp and Krs. Maximum heat transfer rate achieves at Ф = 45°/135°, minimum at Ф = 90°. Abstract: Double diffusive convection in an enclosure partially inserted with heat-generated porous layer and solid layer is investigated numerically. Moist air motions are simultaneously driven by the internal heat generation and external concentration difference imposed across the enclosure. Identical porous and solid layers are attached to the vertical walls, and the walls are held at constant temperatures and concentrations. The horizontal walls of the enclosure are assumed to be adiabatic and impermeable. The aspect ratio of the cavity is equal to 1.0 and the saturating fluid is moist air ( Pr  = 0.7 and Le  = 0.8). Present research covers the range of Rat from 10 3 to 10 7, N from −10.0 to 10.0, Da from 10 −9 to 10 −1, Φ from −90° to 90°, and Krf and Krs from 0.1 to 10.0. The results show that the thermal and solutal buoyancy forces are always aiding with each other and the minus sign of N only has influence on the fluid orientations. For the vertical case, heat and moisture transfer of fluid/porous interface is analyzed as a function of the buoyancy ratio. Average Nusselt and Sherwood numbers are increasing functions of Rat, N, Krp and Krs . Furthermore, volume averaged heat transfer rate as functions of inclination angle, for N  > 0.0, is presented like a sinusoid, where the maximum is near at Ф = 45° and 135°, whereas the minimum is located at Ф = 90°. Present research could benefit future development of sustainable building energy storage.